2020
DOI: 10.1111/jce.14458
|View full text |Cite
|
Sign up to set email alerts
|

Unusual response to His‐refractory atrial premature complex: What is the mechanism?

Abstract: A 32-year-old woman underwent radiofrequency catheter ablation of narrow QRS tachycardia that was terminated with intravenous adenosine. K E Y W O R D S atrioventricular nodal reentrant tachycardia, AVNRT, double supraventricular tachycardias, slow-fast AVNRT, slow-slow AVNRT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…4,5 The termination of tachycardia may provide important clues toward the mechanism of the tachycardia and that close vigilance may clinch the diagnosis before proceeding to other pacing maneuvers. [6][7][8][9][10][11][12] Spontaneous termination with two blocked atrial activations at the end was observed. The termination of the tachycardia with an atrial potential argues also against AT as the mechanism since AT almost always terminates with a QRS complex (Figure 1).…”
Section: Discussionmentioning
confidence: 92%
“…4,5 The termination of tachycardia may provide important clues toward the mechanism of the tachycardia and that close vigilance may clinch the diagnosis before proceeding to other pacing maneuvers. [6][7][8][9][10][11][12] Spontaneous termination with two blocked atrial activations at the end was observed. The termination of the tachycardia with an atrial potential argues also against AT as the mechanism since AT almost always terminates with a QRS complex (Figure 1).…”
Section: Discussionmentioning
confidence: 92%